Keterampilan Motorik dengan Kepercayaan Diri pada Anak Sekolah Dasar - Lubis, Aldi Ali Hamsya; Nuridin Widya Pranoto; Anton Komaini; Nugroho Susanto (Jurnal IKEOR, 2025)
This research seeks to explore how motor abilities are connected to self-assuredness in elementary school children. Motor skills are basic abilities that are important in supporting children’s physical and psychosocial development. Self-confidence as one of the psychological aspects is greatly influenced by children’s experiences in physical activities. This research employs a correlational method that is quantitative in nature. The study’s participants consisted of students of SDN 37 Alang Lawas, with a sample of 22 fifth grade students taken using a purposive sampling technique. Motor skills data were obtained through physical tests, while self-confidence was measured using a Likert scale questionnaire. The results of the analysis showed a significant relationship between motor skills and self-confidence. Children who have good motor skills tend to have higher levels of self-confidence.